Pengaruh Densitas dan Viskositas terhadap Sudut Injeksi Biodiesel Jatropha-Jagung (1:4 dan 4:1) - Wahyudi Wahyudi; Novi Caroko; Hanif Budi Sampurna (JMPM (Jurnal Material dan Proses Manufaktur), 2023)
Biodiesel has attracted attention as an alternative fuel in efforts to reduce emissions and dependence on fossil fuels. Among various potential sources for biodiesel production, jatropha and corn oil have stood out due to their availability and high yield potential. However, each has unique characteristics that affect their performance as fuels. Jatropha oil has relatively high viscosity, while corn oil is generally used as a food ingredient. This study aimed to explore the potential of combining jatropha and corn biodiesel in different proportions and its impact on fuel characteristics and diesel engine spray injection. Both types of oil were processed into biodiesel through esterification and transesterification processes. Subsequently, biodiesel mixtures were created in ratios of 1:4 and 4:1. Each mixture was then varied with diesel to produce B5, B10, B15, B20, B25, B30, B35, and B40. Each sample was tested for its physical properties such as density and viscosity, and injection spray angle. The results of this study indicated that the density and viscosity values of the 1:4 jatropha-corn biodiesel mixture were lower than those of the 4:1 jatropha-corn biodiesel mixture. There was a significant relationship between viscosity and density with the injection angle. The higher the density and viscosity, the narrower the injection angle.